Implementation of Video Tutorial Creation Home Clothing on Practical Elements Manufacturing Clothes and House Fabrics Class XI at SMKN 1 Jabon - Kamaluzzaman, Hani; Arifiana, Deny; Rahayu, Imami Arum Tri; Mayasari, Peppy (Journal of Education Method and Learning Strategy, 2024)
This research aims to 1.) determine the implementation of home clothing-making learning by applying video tutorials, 2.) assess student learning outcomes on home clothing-making material, and 3.) and student responses to applying home clothing tutorial video media on the practical elements of making clothes. Clothing and household linen. This type of research uses pre-experimentation with patterns One Shoot Case Study. The research subjects were 36 class XI Fashion Design students at SMK Negeri 1 Jabon. The data collection method uses observation, student learning outcomes tests, and student response questionnaires, and the data analysis technique used is quantitative descriptive data analysis. The results of implementing learning using video tutorial media obtained a score of 86.20%, which is in the excellent category. Student learning outcomes using video tutorial media were declared complete in KKM with a class average of 84.2% and a classical average of 89%. The student response questionnaire results were 875% in the excellent category. The findings of this research can help students understand the material so that they achieve completeness with a score that exceeds the KKM.